The spellbook library. 2 - Isaki, Uta (A Kodansha reader portal series, 2024)
The continuing story of Yan and Tohru, as they passed teh Spellbook Library's rigorous entrance exam and now regularly manage magical events as part of the library's public relations department working under Emel.